2017
DOI: 10.1042/cs20171118
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cells mediate pathophysiology in response to reduced uterine perfusion pressure

Abstract: Preeclampsia is associated with hypertension, small-for-gestational-age babies, and increased cytolytic natural killer (NK) cells. The specific role of cytolytic NK cells in the pathophysiology of preeclampsia has not been clearly defined. We hypothesized that Reduced Uterine Perfusion Pressure (RUPP) stimulates proliferation and cytolytic activation of NK cells, and that reducing NK cells in RUPP would prevent hypertension, intrauterine growth restriction, and inflammation in response to placental ischemia. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 35 publications
6
54
1
1
Order By: Relevance
“…Additionally, NK depletion improved maternal and fetal outcomes indicating that this activation contributed to the preeclamptic phenotype (Elfarra et al. ). We next performed an adoptive transfer of RUPP stimulated T H 17 cells into normal pregnant animals and saw increased NK cell proliferation and production of cytolytic enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, NK depletion improved maternal and fetal outcomes indicating that this activation contributed to the preeclamptic phenotype (Elfarra et al. ). We next performed an adoptive transfer of RUPP stimulated T H 17 cells into normal pregnant animals and saw increased NK cell proliferation and production of cytolytic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously demonstrated that depletion of NK cells in the RUPP model improves both maternal and fetal outcomes (Elfarra et al. ). In addition, we have shown that adoptive transfer of RUPP stimulated T H 17 cells into normal pregnant animals induces a preeclamptic phenotype and results in significantly increased cNK cell populations (Cornelius et al.…”
Section: Introductionmentioning
confidence: 99%
“…A reduced uterine perfusion pressure rat model led to the conversion of tolerogenic dNKs to a cytolytic phenotype. This shift was associated with higher mean arterial pressure, fetal intrauterine growth restriction (FUGR), and increased inflammation, changes that were reversed by the depletion of NK cells …”
Section: Mechanisms Of Preeclampsiamentioning
confidence: 99%
“…Risk factors for preeclampsia 2 pressure rat model led to the conversion of tolerogenic dNKs to a cytolytic phenotype. This shift was associated with higher mean arterial pressure, fetal intrauterine growth restriction (FUGR), and increased inflammation, changes that were reversed by the depletion of NK cells 15. 4.2 | Inadequate remodeling of spiral uterine arteries by cytotrophoblast cellsThe first observations of SUA remodeling in pregnancy came from placental biopsy specimens acquired during cesarean sections.…”
mentioning
confidence: 99%
“…A rodent experiment demonstrated that an increase in cytolytic NK cells in PE is directly related to high blood pressure and foetal uterine growth restriction. The study found that RUPP induced the activation and proliferation of cytolytic NK cells in mice and that the depletion of NK cells in mice prevented placental ischaemia induced high blood pressure, intrauterine growth restriction and inflammation …”
Section: Innate Immunitymentioning
confidence: 98%